2013
DOI: 10.1017/s0022149x13000345
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent paediatric pinworm infection of the vagina as a potential reservoir for Enterobius vermicularis

Abstract: Enterobius vermicularis infection remains one of the most common parasitic infections, particularly prevalent in children. Enterobiasis, although not usually dangerous, may cause significant morbidity. Elimination of the parasite from a family or an institution often poses problems, either because of an incomplete cure or re-infection. While there have been limited reports of ectopic enterobiasis throughout the world, ours is probably one of the rarest reports of recurrent vaginal E. vermicularis infection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…There were no gastrointestinal symptoms, and repeated stool samples of the patient and her family were negative. In this case, recurrent vaginal infection by EV despite treatment and in the absence of any signs of gastrointestinal infection suggests that the vagina is a potential reservoir …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There were no gastrointestinal symptoms, and repeated stool samples of the patient and her family were negative. In this case, recurrent vaginal infection by EV despite treatment and in the absence of any signs of gastrointestinal infection suggests that the vagina is a potential reservoir …”
Section: Discussionmentioning
confidence: 83%
“…The frequency of involvement of the genital tract is unknown because only scarce reports of extraintestinal enterobiasis, in the ovary, vagina, salpinx, and peritoneal cavity can be found in the available literature . Concerning findings of EV in the vagina reported throughout the world, the literature in English contains ∼30 cases of EV, mostly EV eggs, discovered in vaginal or cervical smears, since the 1970 s (Table ) . Interestingly, the majority of the cases reported come from India, even though enterobiasis seems more prevalent in temperate than tropical countries .…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may be asymptomatic, with reports of ova in vaginal smears in patients without any symptoms until the infestations were severe enough to cause uterine enlargement and pelvic pain . Kashyap et al . reported a case of vulvar itching in a patient with live worms found in the vagina on multiple occasions.…”
Section: Enterobiusmentioning
confidence: 99%
“…Some patients may be asymptomatic, with reports of ova in vaginal smears in patients without any symptoms until the infestations were severe enough to cause uterine enlargement and pelvic pain. 62 Kashyap et al 63 reported a case of vulvar itching in a patient with live worms found in the vagina on multiple occasions. This patient experienced no perianal itching, no worms or ova located in the gastrointestinal tract or GI symptoms, and repeated negative tape tests, with authors concluding that the vagina can serve as the sole reservoir for these worms.…”
Section: Clinical Presentation and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation